VD_FINDINFO HC / 2024 / 290 vom 26. April 2024 - VD Tribunal cantonal (2024)
DÉCISION, PREUVE, DOMMAGE IRRÉPARABLE, EXPERTISE PSYCHIATRIQUE, CURATELLE ÉDUCATIVE | 307 al. 1 CC, 307 al. 3 CC, 154 CPC (CH)